Surface plasmon polaritons in hyperbolic nanostructured metamaterials. Issue 14 (22nd September 2018) - Trofimov, Aleksej; Gric, Tatjana
Abstract: Here, new kinds of surface waves on nanostructured metamaterial (MM), crossing the light line with a substantial portion at lower frequencies lying above the free space light line, are considered. We present the numerical study of dispersion features of hyperbolic MMs for various cases, and the tunability of hyperbolic MMs based on grapheme-dielectirc multilayers and transparent conducting oxide-dielectric multilayers have been demonstrated. Similar to grapheme-dielectric MM, the propagation of the new surface waves on nanostructured MM presented in this manuscript is sensitive and can be controlled by the parameters of the materials employed in nanostructures. Remarkably, the parameters of the materials employed in nanostructures dramatically influence the propagation of such surface waves. Additionally, the Ferrell–Berreman modes are detected under certain conditions, providing a fertile ground for device fabrications.